2017
DOI: 10.1002/jcb.25882
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin Binding to Death Receptor 5-mediated Death-Inducing Signaling Complex in Breast Cancer Cells

Abstract: Activation of death receptor-5 (DR5) leads to the formation of death inducing signaling complex (DISC) for apoptotic signaling. TRA-8, a DR5 specific agonistic antibody, has demonstrated significant cytotoxic activity in vitro and in vivo without inducing hepatotoxicity. Calmodulin (CaM) that is overexpressed in breast cancer plays a critical role in regulating DR5-mediated apoptosis. However, the mechanism of CaM in regulating DR5-mediated apoptotic signaling remains unknown. In this study, we characterized C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
(65 reference statements)
0
6
1
Order By: Relevance
“…Since Bex1 has been shown to interact with many different proteins, several potential mechanisms, independent of p75 NTR signaling, are suggested by previous work. For example, BEX1 has been reported to bind Calmodulin (65), BAG4/SODD, and Caspase 8 (70), all of which have roles in death signaling through DISC (71)(72)(73). In contrast to our observations, Bex1 has been shown to have a pro-apoptotic role by binding to Bcl2 in cancer cells (74).…”
Section: Discussioncontrasting
confidence: 83%
“…Since Bex1 has been shown to interact with many different proteins, several potential mechanisms, independent of p75 NTR signaling, are suggested by previous work. For example, BEX1 has been reported to bind Calmodulin (65), BAG4/SODD, and Caspase 8 (70), all of which have roles in death signaling through DISC (71)(72)(73). In contrast to our observations, Bex1 has been shown to have a pro-apoptotic role by binding to Bcl2 in cancer cells (74).…”
Section: Discussioncontrasting
confidence: 83%
“…Our recent studies demonstrated that CaM directly bound to DR5 in a Ca 2+ -dependent manner and CaM bound to DR5mediated DISC for apoptosis in TRA-8 sensitive triple negative MDA-MB-231 and ER-positive ZR-75-1 breast cancer cells. 36,65 We demonstrated that CaM antagonist, TFP, inhibited CaM recruitment into DISC, decreased TRA-8 activated DR5 oligomerization, attenuated DISC formation, and reduced TRA-8 activated caspase-dependent apoptotic signaling and TRA-8 induced cytotoxicity in TRA-8 sensitive MDA-MB-231 or ZR-75-1 breast cancer cells. However, in this study for TRA-8 resistant TNBC cell lines, we observed that CaM antagonists increased TRA-8 induced cytotoxicity in a concentration and time-dependent manner.…”
Section: Discussionmentioning
confidence: 88%
“…[31][32][33][34] Our recent studies have shown that CaM directly binds to DR5 in a Ca 2+ dependent manner and CaM binding to DR5-mediated DISC to signal apoptosis in TRA-8 sensitive ER-positive and triple negative breast cancer cells. 35,36 An earlier study show that tamoxifen, one of the CaM antagonists, induces apoptosis via ERβ in TRA-8 sensitive basal B TNBC, and combined tamoxifen and TRA-8 treatment for TRA-8 sensitive basal B TNBC showed an antagonistic effect for antitumor effect. 37 Understanding the role of CaM and CaM antagonist in regulating DR5-induced DISC formation for apoptosis in TRA-8 resistant TNBC could lead to the identification of novel strategies and drug targets, including more specific and potent agent development, for enhancing apoptosis to overcome drug resistance for TNBC treatment.…”
mentioning
confidence: 99%
“…Since Bex1 has been shown to interact with many different proteins, several potential mechanisms, independent of p75 NTR signaling, are suggested by previous work. For example, BEX1 has been reported to bind Calmodulin 64 , BAG4/SODD, and Caspase 8 69 , all of which have roles in death signaling through DISC 7072 . In contrast to our observations, Bex1 has been shown to have a pro-apoptotic role by binding to Bcl2 in cancer cells 73 .…”
Section: Discussionmentioning
confidence: 99%